The effects of aluminum on growth and uptake of Al and P by rice - Fageria, N. K.; Baligar, V. C.; Wright, R. J. (Pesquisa Agropecuaria Brasileira, 2014)
Aluminum toxicity is an important factor limiting plant growth in acid soils. The effect of five Al levels (0, 371, 742, 1484, and 2226 μM) in nutrient solution on the growth and uptake of Al and P by two rice cultivars (Suvale 1 and IRGA 408) was studied. Aluminum reduced root and shoot growth in both, cultivars, but the reduction was greater in IRGA 408. Aluminum uptake was increased with increasing levels of Al in the two cultivars. The effect was greater in the roots as compared to the shoots. The tolerant cultivar Suvale 1 absorbed more phosphorus to susceptible cultivar IRGA 408. The uptake and use efficiency of P was highly correlated with the growth of the rice plant. Toxic Ali level in the nutrient solution were 260 μM for shoot growth and 280 μM for root growth, respectively.
Keywords: Al toxicity; nutrient solution; root growth; shoot growth